Tobacco Cessation May Improve Lung Cancer Patient Survival - Dobson Amato, Katharine A. (J Thorac Oncol, 2015)
INTRODUCTION: This study characterizes tobacco cessation patterns and the association of cessation with survival among lung cancer patients at Roswell Park Cancer Institute: an NCI Designated Comprehensive Cancer Center. METHODS: Lung cancer patients presenting at this institution were screened with a standardized tobacco assessment, and those who had used tobacco within the past 30 days were automatically referred to a telephone-based cessation service. Demographic, clinical information and self-reported tobacco use at last contact were obtained via electronic medical records and the RPCI tumor registry for all lung cancer patients referred to the service between October 2010 and October 2012. Descriptive statistics and Cox proportional hazards models were used to assess whether tobacco cessation and other factors were associated with lung cancer survival through May 2014. RESULTS: Calls were attempted to 313 of 388 lung cancer patients referred to the cessation service. Eighty percent of patients (250/313) were successfully contacted and participated in at least one telephone-based cessation call; 40.8% (102/250) of persons contacted reported having quit at the last contact. After controlling for age, pack year history, sex, ECOG performance status, time between diagnosis and last contact, tumor histology, and clinical stage, a statistically significant increase in survival was associated with quitting compared to continued tobacco use at last contact (HR=1.79; 95% CI: 1.14-2.82) with a median 9 month improvement in overall survival. CONCLUSIONS: Tobacco cessation among lung cancer patients after diagnosis may increase overall survival.